Preparation of Administrative Cost Budgeting with Maqasid Syariah Approach: Case Study at Kspps Tunas Artha Mandiri Nganjuk - Isnaini, Ulya Nur; Salma, Fitria Solahika; Sujianto, Agus Eko (Formosa Journal of Multidisciplinary Research, 2024)
The budget for administrative costs is indicative of the well-being within the company. According to Islamic economic principles, the primary objective is to attain comprehensive prosperity, encompassing material, spiritual, and moral well-being. The concept of prosperity and happiness (falah) aligns with the tenets of Islamic sharia, which consist of five principles of maqasid sharia: religion (ad-ddin), soul (an-nafs), reason (al-aql), heredity (an-nasl), and assets (al-mal) (Suardi, 2021). In the realm of Islamic economics, the maqasid sharia approach can guide budget formulation to align with Islamic values, emphasizing public welfare, justice, and sustainability.